Should the unemployed care for the elderly? The effect of subsidized occupational and further training in geriatric care - Julia Lang; Christine Dauth (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This study analyzes the effectiveness of subsidized training in elderly care professions for the unemployed in Germany. We find that shorter further training increases employment but hardly affects wages. Retraining, which entails a vocational degree as geriatric nurse, causes strong lock-in effects, but afterwards substantial positive wage and employment effects that exceed those of further training. Yet, large shares of the estimated employment effects are attributable to part-time employment.
Keywords: I11; J24; J68; 330